SIMULATION ANALYSIS OF THE QUEUE AT THE PORT CONTAINER SHIPS WITH SEVERAL SERVICE TIME DISTRIBUTION - A.A.P. MAITIMU (NIM : 20113057), FRANSISKA
Queuing theory is a study related to the behaviour of the queuing system, which is occupied to measure the performance of a service time. The queue of service system can be modeled by queuing model in order to see the pattern of arrival, service, and waiting time of the ships. This thesis using three models, that are M/G/∞, M/M/m, and M/Ek/m. Futhermore, Little's Formula is used to see the performance of these queue models. Some simulations were executed to give some illustrations, by using the information of time arrival of the container ships at the port (rate is 0.3718 ship/day). There are three servers and the service time is two until four days. Based on those informations, it is illustrated some several systems that are possible happenend in the port. It is also obtained the waiting time and numbers of ship in the system.